English language proficiency requirements in university conditional admission: A case study of a pathway program - Hoekje, Barbara; Harman, Travis; Heitner, Reese (Journal of Academic Language and Learning, 2021)
English language proficiency is typically measured through standardized tests such as TOEFL or IELTS. Standardized test scores are “boundary objects” that allow stakeholders to communicate about the abstract concept of language proficiency. Other means of measurement are possible, but there has been little consideration of how their merits can be evaluated. We describe a university conditional admission “pathway” program in the United States that combines language study, disciplinary credit courses, test preparation, and acculturation activities. During three academic years (AY 2014-15, 2015-16, and 2016-17), 161 students (most from China) enrolled in the pathway with 97 matriculating as first-year students, an overall matriculation rate of 60%. Subsequent performance in the university was high, with average first-year grade point averages statistically equivalent to those of their directly admitted international peers; first-year persistence and six-year graduation rates were higher than those of the overall university population. Initially, pathway participants were required to reach standardized test scores as well as program performance standards in order to matriculate. However, as successive pathway cohorts developed a track record of matriculated performance and persistence, program administrators sought alternate exit evaluation measures. Here, we describe (i) our language proficiency construct (“communicative language proficiency for university study”); (ii) curricular affordances provided for developing this proficiency; (iii) measures of performance collected pre- and post-matriculation among program participants; and (iv) the consequential validity of standardized test requirements. We conclude that program performance measures are preferable to standardized test scores as indicators of college readiness in a university-governed conditional admission program after an initial standardization period.